ICT Implementation for Improving Communication among SME Contractors in Construction Industry - Chua, Xin Jie; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam (Research in Management of Technology and Business, 2022)
The lack of efficient communication and data exchange between SME contractors is a major contributor to poor performance in the construction industry. Small and medium-sized enterprises (SMEs) lacked dynamism compared to large-scale construction companies. Therefore, the purpose of this research is to enhance ICT implementation for improving communication between SME contractors. The objectives of this research are to investigate current practices, challenges, and influencing factors of ICT implementation to improve communication between SME contractors in the construction industry. To achieve the objectives of this research, secondary data thorough literature review was conducted and primary data were gathered through a quantitative approach. The respondents of this study involved SME contractors in Sabah. The respondents from SME contractors involved project managers, site managers, supervisors, and engineers with 134 respondents from G1 and 122 respondents from G2. The greatest frequency and mean score values were determined using IBM SPSS Statistic 26 software. Based on the findings, the highest mean for current practices of ICT implementation was E-mail and Short Message Services. The challenges of ICT implementation were a budget constraint for ICT investment and for influencing factors of ICT implementation were reliable telecommunication networks or telephone lines.  In conclusion, this study adds to the understanding that ICT implementation might improve communication between SME contractors in the construction industry.